2022
DOI: 10.3390/math10162899
|View full text |Cite
|
Sign up to set email alerts
|

A Path Planning Model for Stock Inventory Using a Drone

Abstract: In this study, a model and solution are shown for controlling the inventory of a logistics warehouse in which neither satellite positioning nor IoT solutions can be used. Following a review of the literature on path planning, a model is put forward using a drone that can be moved in all directions and is suitable for imaging and transmission. The proposed model involves three steps. In the first step, a traversal path definition provides an optimal solution, which is pre-processing. This is in line with the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Today, cloud-based services are increasingly popular for drone work [13], [14]. It provides a good solution for the storage and processing of data collected by drones in the case of inventory control [15], [16].…”
Section: Resultsmentioning
confidence: 99%
“…Today, cloud-based services are increasingly popular for drone work [13], [14]. It provides a good solution for the storage and processing of data collected by drones in the case of inventory control [15], [16].…”
Section: Resultsmentioning
confidence: 99%
“…Based on a quadrotor drone, they proposed a route-planning method that uses a drone equipped with an RFID reader to carry out inventory of industrial product warehouses. Since the particle swarm optimization algorithm (PSO) tends to converge prematurely when solving routing problems and tends to fall into local optima (which, according to our experience [23], often happens), PSO is improved and a differential evolution based a repair method is suggested. The fitness-adaptive differential evolution algorithm (FiADE) and PSO were mixed (used previously [24,25]) and further developed for further application in three-dimensional space.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to solve the inventory task, it is necessary to examine which drones are suitable for performing the task. Our previous investigations [23] showed that autonomous drones are needed for the task. For a drone to be fully autonomous, the ability to localize is very essential.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations